(untitled) (Research, Society and Development, 2022)
Objective: to report the actions performed to minimize risk factors for obesity in the adult population assisted in a family health unit. Method: experience report of the educational actions implemented in a family health unit, in the city of Salvador, Bahia, from 2017 to 2018. With the participation of the adult population of the enrolled region and health professionals. Actions were carried out such as: health education in the office, nas health fairs and during the reception session with qualified listening of users, in the corridor/ waiting room and in the community with the help of Community Health Agents, through the capture of cases. Results: the actions adopted provided means for the construction of the relationship between ff users with the services offered. Reinforcing the importance of primary care in recognizing the community’s health needs, as well as the identification of obese individuals, for proper treatment and referrals to specialized services according to the demand found. Final considerations: the use of strategies to raise awareness of obesity in adults, boosted health education, bringing professionals inserted in this context closer to the community. Fostering discussions about the real health needs of this population, as well as the use of resources that enable the fulfillment of their demands.